Contrasting functional traits explain differences in lianas between restored and native forests - Dalbeto, Andra Carolina [UNESP]; Machado, Deivid Lopes [UNESP]; Engel, Vera Lex [UNESP] (Springer Nature, 2025)
Lianas have often been neglected in the restoration of tropical forests, although they are key components of these communities. Compositional differences between restored and reference forests have been observed for lianas, although this pattern is not entirely understood. We evaluated liana communities naturally recruiting in four 20-year-old assisted restoration treatments and an old-growth tropical semideciduous forest in the Atlantic Forest, southeastern Brazil. We evaluated tree structure and censused all liana stems ≥ 2 cm diameter at breast height. Leaf mass per area (LMA), wood density, seed dispersal syndromes and climbing mechanisms were assessed for the liana species. We found no difference in the density and species richness of lianas across restoration treatments, nor between the restored and the reference forests. Liana abundance in the reference forest was associated with higher tree density and deciduousness, whereas in the restored forests, it was primarily influenced by canopy openness. Liana species composition differed between the restored and the native forest, reflecting functional differences. Liana LMA was 27% higher and wood density 5% lower in the restoration treatments than in the reference forest. The restoration treatments showed a higher proportion of anemochorous species compared to the reference forest, while the reference forest displayed higher proportions of zoochorous and autochorous species. The reference forest exhibited a higher frequency of scramblers and tendril climbers, whereas twiners dominated the restoration treatments. Functional traits and habitat preferences show that lianas adopt an acquisitive resource strategy in restored forests, contrasting with a conservative strategy in well-preserved forests.